Studi kasus analisis kemampuan pemecahan masalah matematis ditinjau dari peningkatan self-efficacy - Putri, Maria Rosari Sulistyo; Martadiputra, Bambang Avip Priatna (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2025)
Problem solving abilities can help students to improve their analytical power and help them to apply mathematics to various situations. Students who have good intentions in learning tend to be more diligent and tenacious in understanding and solving mathematical problems, even difficult mathematical problems. This is related to the affective aspect of students, namely self-efficacy. This research uses a qualitative approach and data collection techniques are carried out through filling out self-efficacy questionnaires, problem solving ability tests, and interviews. The results of this research are that students with a high level of self-efficacy have a fairly high level of problem solving ability even though not all indicators have been met, students with low and medium levels of self-efficacy have a low level of problem solving ability with only one or two indicators being met fulfilled.